PENGEMBANGAN INSTRUMEN ASESMEN KETERAMPILAN MENULIS TEKS EKSPOSISI - Siti Nur Afifatul Hikmah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Assessment is an assessment tool used by teachers in learning. assessment has a broad scope of assessment. Teachers use assessments to determine the level of mastery of the competencies being taught. Instruments developed by teachers should be tested for quality to produce data that can be accounted for. With an assessment, the teacher can find out the advantages and disadvantages in a learning process of exposition writing assessment carried out by the teacher, either in the form of teaching methods or teaching strategies applied during the learning process. The assessment should be carried out with good and appropriate planning under the learning objectives.